1987
DOI: 10.1002/pssa.2211020203
|View full text |Cite
|
Sign up to set email alerts
|

Defects and Oxygen in Silicon Studied by Positrons

Abstract: During the last few years wide interest is generated in applying the positron annihilation techniques to defects in semiconductors. Since defects in semiconductors are, in many regards, dissimilar to defects in metals one must expect that new responses from positrons will emerge not normally associated with metals. One such important effect would be the charged state of a defect in a semiconductor. At the present time silicon is the semiconductor which has been investigated mostly, but the important 111-V GaAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(24 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…The data can also be fitted by our assuming no electric field and a uniform (dilute) concentration of defects in the overlayer (vC = 3x 10 9 ; S D /S B = 1.03), although the X 2 is in this case slightly higher. By use of the specific trapping rate obtained for point defects in silicon by positron lifetime techniques 21,22 (v-3xl0 14 s _1 ), the above implies a defect concentration of C-10 ~~5. Given the systematic limitations of the present experiment (e.g., stopping-profile uncertainties, statistic, etc.…”
mentioning
confidence: 96%
“…The data can also be fitted by our assuming no electric field and a uniform (dilute) concentration of defects in the overlayer (vC = 3x 10 9 ; S D /S B = 1.03), although the X 2 is in this case slightly higher. By use of the specific trapping rate obtained for point defects in silicon by positron lifetime techniques 21,22 (v-3xl0 14 s _1 ), the above implies a defect concentration of C-10 ~~5. Given the systematic limitations of the present experiment (e.g., stopping-profile uncertainties, statistic, etc.…”
mentioning
confidence: 96%
“…These lifetimes are shorter than those obtained as an intermediate lifetime component in the present work, which suggests that the defects in hydrogen-doped alkali-metal fullerides are not monovacancy, but higher-order one. The lifetime of positrons in the surface state has been reported to be 0.400 ns for a hydrogenated carbon film [15], 0.45 ns for graphite [16] and longer than 0.520 ns for a 6-vacancy cluster in Si [17]. From these results, it is concluded that hydrogen-doping to alkalimetal fullerides increases the concentration of higher-order vacancy-type defects, through which more than 50% injected positrons annihilate.…”
Section: Resultsmentioning
confidence: 78%
“…For fluences greater than 6ϫ10 15 cm Ϫ2 , the density of defects 1 and 2 is at least 1ϫ10 19 and 2.5ϫ10 19 cm Ϫ3 , respectively, whereas for 4ϫ10 15 cm Ϫ2 the density of defect 2 falls to 1.5ϫ10 19 cm Ϫ3 . For fluences of 1ϫ10 15 and 2ϫ10 14 cm Ϫ2 , only defect 1 is present at concentrations of 1ϫ10 19 and 2ϫ10 18 cm Ϫ3 , respectively. If there exists a built-in electric field as speculated in Sec.…”
Section: Defect Distributionmentioning
confidence: 98%